State of vulnerable populations in the techquity framework in Hungary - Győrffy, Zsuzsa; Döbrössy, Bence; Radó, Nóra; Boros, Julianna; Békási, Sándor (Frontiers in Public Health, 2023)
Digital health solutions could alleviate the needs of vulnerable populations in the recent period of the permacrisis, however, there are several barriers that limit their use for certain individuals. We use the four-pillar model of the novel concept of techquity to provide original evidence of the discrepancy in the willingness to try and the ability to harness healthtech in Hungary. We identified three underserved segments of society: older adults, people with long-term activity-limiting conditions, and people experiencing homelessness who could greatly benefit from digital technologies and yet use them less than the general population. We also discuss potential strategic considerations in order to promote techquity and digital inclusion among people living in vulnerable situations.